Recent advances in animal nutrition, 1987 - Haresign, William; Cole, D. J. A. (Studies in the agricultural and food sciences., 1987)
Recent Advances in Animal Nutrition - 1987 focuses on the advancement of techniques, procedures, and processes in animal nutrition. The selection first discusses techniques for identifying the metabolizable energy (ME) content of poultry feeds and the impact of declaration of ME value of poultry feeds. Methods for determining the ME of feeds; formulation of products and declaration of energy; species and ages of birds; and analytical problems are considered. The book also discusses the effects of diarrhea and wet litter in meat poultry; the inclusion of phosphorus in the diet of laying hens; n.